Physicochemical and labelig analysis of brazilian commercial brands of fruit nectar with apple juice like as a sweetener (Research, Society and Development, 2023)
The consumption of sugar and sugary products has increased worldwide in recent years and this has been reflected in the increase in chronic non-communicable diseases. Seeking alternatives to reduce added sugar in foods and beverages and valuing the sensory quality of products, many strategies have been used today, including the addition of apple juice to fruit drinks. Based on this need, the aim of this study was to elucidate the labeling information and the physicochemical characteristics of mixed nectars that use apple juice as a sweetening ingredient. Labels of 36 brands of fruit drinks were analyzed, of which 66.7% were mixed products with apple juice. Of mixed products, 79.2% had additional information about the use of apple juice in the product's composition. In the physical-chemical analysis, five brands were selected and the analyzes of pH, total soluble solids, titratable acidity, and glycides were carried out. There was variability between samples for all parameters, even if they had the same flavor and percentage of declared total juice. These results demonstrate how products that have the same definition and for the consumer the same apparent composition, a physical-chemical and nutritional variability, pointing to the need to better understand these products added with apple.